2016
DOI: 10.1007/s11910-015-0619-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Targeted Temperature Management in Acute Brain and Spinal Cord Injury

Abstract: Acute brain and spinal cord injuries affect hundreds of thousands of people worldwide. Though advances in pre-hospital and emergency and neurocritical care have improved the survival of some to these devastating diseases, very few clinical trials of potential neuro-protective strategies have produced promising results. Medical therapies such as targeted temperature management (TTM) have been trialed in traumatic brain injury (TBI), spinal cord injury (SCI), acute ischemic stroke (AIS), subarachnoid hemorrhage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Approximately 1.7 million individuals worldwide suffer from SCI each year [94], with increases health care and living expenses [95]. It has been suggested that miRNAs regulate gene expression and are associated with the pathogenic processes of SCI, such as inflammation, oxidation, demyelination, and apoptosis [96].…”
Section: Combination Of Rnai and Stem Cells For Treatment Of Cns Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 1.7 million individuals worldwide suffer from SCI each year [94], with increases health care and living expenses [95]. It has been suggested that miRNAs regulate gene expression and are associated with the pathogenic processes of SCI, such as inflammation, oxidation, demyelination, and apoptosis [96].…”
Section: Combination Of Rnai and Stem Cells For Treatment Of Cns Dmentioning
confidence: 99%
“…Currently, standard therapies only have limited effects on secondary neuronal injury [94]. Thus, strategies for treatment and prevention of secondary neuronal damage are necessary.…”
Section: Combination Of Rnai and Stem Cells For Treatment Of Cns Dmentioning
confidence: 99%